Reversible Modulation of Myofibroblast Differentiation in Adipose-Derived Mesenchymal Stem Cells - Desai, Vivek D. (Public Library of Science, 2014)
Unregulated activity of myofibroblasts, highly contractile cells that deposit abundant extracellular matrix (ECM), leads to fibrosis. To study the modulation of myofibroblast activity, we used human adipose-derived mesenchymal stem cells (ADSCs), which have much potential in regenerative medicine. We found that ADSCs treated with TGF-β developed a myofibroblastic phenotype with increases in α-smooth muscle actin (α-SMA), a myofibroblast marker, and ECM proteins type I collagen and fibronectin. In contrast, treatment with bFGF had the opposite effect. bFGF-differentiated ADSCs showed marked down-regulation of α-SMA expression, collagen I, and fibronectin, and loss of focal adhesions and stress fibers. Functionally, bFGF-differentiated ADSCs were significantly more migratory, which correlated with up-regulation of tenascin-C, an anti-adhesive ECM protein, and vimentin, a pro-migratory cytoskeletal protein. On the other hand, TGF-β-differentiated ADSCs were significantly more contractile than bFGF-differentiated cells. Interestingly, cells completely reversed their morphologies, marker expression, signaling pathways, and contractility versus migratory profiles when switched from culture with one growth factor to the other, demonstrating that the myofibroblast differentiation process is not terminal. Cell differentiation was associated with activation of Smad2 downstream of TGF-β and of ERK/MAP kinase downstream of bFGF. Reversibility of the TGF-β-induced myofibroblastic phenotype depends, in part, on bFGF-induced ERK/MAP kinase signaling. These findings show that ADSC differentiation into myofibroblasts and re-differentiation into fibroblast-like cells can be manipulated with growth factors, which may have implications in the development of novel therapeutic strategies to reduce the risk of fibrosis.